Determinants of Market Capitalization and Effect on Sharia Stock Returns in the Jakarta Islamic Index - Akidah Fitrah; Gaguk Apriyanto; Harianto Respati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The aims of this study is to test and obtain empericial evidence regarding the effect of the effect of EPS, EPS, ROA, ROE, ROI, Inflation, Interest Rate, Exchange Rate Rupiah against USD and Indonesian Crude Price on Market Capitalization and the mediating effect of Market Capitalization on Stock Returns Jakarta Islamic Index Indonesia. This study is a causal study with a quantitative approach. The sample was selected by purposive sampling. The data used is secondary data. Dana analysis used data panel regression. Based on results of study, various empirical evidences were found. EPS, PER, ROA and ROE has a positive effect and significant on Market Capitalization. ROI and Interest Rate has a negative effect and significant on Market Capitalization. Inflation and Indonesian Crude Price has a positive and insignificant on Market Capitalization. Exchange Rate Rupiah against USD has a negative effect and insignificant on Market Capitalization. Market Capitalization has a negative and insignificant on Stock Returns. The Market Capitalization cannot as a information for investors in predicting stock returns, because the Market Capitalization is not necessarily able to provide high stock returns.